(untitled) - Neill, Sean (London, 1993)
The book is intended for new classroom teachers, including licensed and articled teachers, and those who advise and train them. Here an educational researcher and a classroom teacher join forces to show new teachers in particular how to use effectively gesture, posture, facial expression and tone of voicce to establish a good relationship with the class they teach. Each chapter is illustrated with clear drawing of pupils and teachers in common classroom situations and accompanied by training exercises aimed at improving the new teacher's ability observe both her class and her own practice
Keywords: interaction analysis in education,nonverbal communication in education - gt.britain - problems, exercises